The Effect of SMEs’ Digitalization on Supply Chain Financing Performance: Based on the Resource Orchestration Theory - Qiang Lu; Wangzhe Qin; Rui Yan; Songbo Zhang; Lianyao Ma (Journal of Theoretical and Applied Electronic Commerce Research)
This study aims to use resource orchestration theory (ROT) to investigate how small and medium-sized enterprise (SME) digitalization affects supply chain financing performance (SCFP) by examining the mediation effect of ambidextrous innovations. It also investigates the moderating role of environmental competitiveness on the relationship between SME digitalization and SCFP, and ambidextrous innovations, respectively. A valid representative sample for this study was drawn from 343 Chinese SMEs through a questionnaire survey. Multiple regression analysis was used to test the hypotheses. The study revealed a positive impact of SMEs’ digitalization on SCFP. Meanwhile, exploitative innovation, not exploratory innovation, plays a partial mediating role between SMEs’ digitalization and SCFP. Environmental competitiveness strengthens the positive relationship between SMEs’ digitalization and SCFP. Moreover, environmental competitiveness strengthens the positive relationship between SMEs’ digitalization and exploratory innovation. This study is one of the first to identify digitalization as a key antecedent of SCFP and the mediating role of ambidextrous innovations on the relationship between SMEs’ digitalization and SCFP. Also, this is the first study to explore the moderating role of environmental competitiveness in the context of digitalization.